PCB118-Induced Cell Proliferation Mediated by Oxidative Stress and MAPK Signaling Pathway in HELF Cells - Muhammad Zaffar Hashmi; Ahmad Hasnain; Jabir Hussain Syed; Muhammad Tariq; Xiaomei Su; Hussani Mubarak; Wajid Nasim; Chaofeng Shen (SAGE Publishing, 2018)
The present study used human lung fibroblast (HELF) cells as a test model to evaluate the role of oxidative stress (OS) and extracellular signal-regulated kinases 1/2 (ERK1/2) protein in HELF cell proliferation exposed to PCB118. Results from 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide demonstrated that PCB118 at lower concentrations stimulated proliferation of HELF cell and abrogate proliferative effect at higher dose concentrations and in a time-dependent manner. Moreover, reactive oxygen species, malondialdehyde (MDA), and superoxide dismutase showed a significant increase at higher concentrations of PCB118 than the lower concentrations with the passage of time. Antioxidant enzymes such as glutathione peroxidase exhibited decreasing trends in dose- and time-dependent manner. Lipid peroxidation assay resulted in a significant increase in MDA level in PCB118-treated HELF cells compared with controls, suggesting that OS plays a key role in PCB118-induced toxicity. Comet assay indicated a significant increase in genotoxicity at higher concentrations of PCB118 exposure than the lower concentrations. It was found that PCB118 showed expression of ERK1/2 protein after 4 hours, while after 48 hours, the protein expression was less, indicating PCB toxicity to MAPK protein of HELF cell. Oxidative stress, ERK1/2, and HELF cell proliferation exhibited correlation. The results will elaborate toxicological evaluation of PCB118 to HELF cells and will help to develop drug for PCB-induced diseases.